“Wetland” como unidade hidrogeomorfológica na transição entre o cerrado e o semiárido mineiro: análise da dinâmica do Pantanal da bacia de drenagem do rio Pandeiros - MG - Diego Alves de Oliveira (2019)
The Pantanal of Pandeiros River (PRP), located in the northern region of Minas Gerais, Brazil, is an important wetland for the São Francisco River watershed, partially contributing to carbon trapping and containment of sediments transported to the São Francisco River, which, otherwise, they would contribute to silting. Resulting from the interaction between several factors such as geology, geomorphology, and climatic variations in a transition region from a humid tropical area to the semiarid region, its main source of moisture is the monsoons that occur in South America, which enable the occurrence of flood pulses, temporarily changing its base levels and allowing the flooding of wetlands, demonstrating the importance of its analysis through a hydrogeomorphological approach. The main objective of the research is to understand the dynamics of this wetland as a hydrogeomorphological unit and not just an ecosystem, as it usually occurs in the literature. Analysis of flood pulses was performed using data from fluviometric and climatological stations installed in the PRP, which showed cyclical variations in the moisture supply. The results indicate that in recent years, a reduction in the level of the São Francisco River and the flow of the Pandeiros river was registered, implying a reduction in the PRP flooding in all aspects investigated: duration, frequency, intensity, and magnitude, mainly from the 1990s. The change in the base level, in this case, the level of the São Francisco River at the mouth of the Pandeiros river, is an important factor because through the analysis of Digital Elevation Models with a resolution of 12.5 m it was possible to identify that the wetland is topographically a depression whose altitude is largely like that of the São Francisco River channel, which implies in flooding much more longitudinal than lateral in the PRP. Techniques were applied to characterize the geochemical signature of surface water, such as pH, alkalinity, electrical conductivity (EC), total dissolved solids, turbidity, silica, and ICP analysis, which revealed an abundance of dissolved calcium and magnesium. The dynamics of water circulation using 2H and 18O isotopic tracers demonstrated the interactions that occur at the mouth of the Pandeiros river during the different phases of flooding. The longitudinal monitoring of the water level along the PRP area was carried out with the monitoring of 5 piezometers whose data, analysed together with the other techniques, indicated the existence of four different hydrogeomorphological units within the PRP. In each of these, samples were taken from the regolith, submitted to laboratory analysis of particle size, pH, EC, organic carbon (CO), sodium, potassium, aluminium, iron, calcium, and magnesium, which also show lateral and mainly longitudinal variation along of the PRP. Subsurface, using ground penetrating radar, the predominance of horizontal layers was identified; however, from 3 - 4 m deep, there are several paleochannels and angular pebbles, indicating a high energy environment during the deposition period. The denudation dynamics of the Pandeiros river watershed was also analysed, using 10Be, with an estimate of the average loss of altered material per million years (Ma) in four points of the basin, indicating a large contribution of sediments from the escarpment of dissection of the chapadas that surround a good part of the Pandeiros river watershed and that were, and continue to be, directed to the PRP. Organic sediments at 150 cm depth were also dated using 14C (TPM), which showed ages of up to 3,246 years A.P. and deposition in a very humid, relatively constant paleoclimatic environment, as indicated by the 13C isotopic composition. The results indicate that this wetland is dependent on multiscale conditions, in a complex hydrogeomorphological dynamic, in a situation of subtle environmental equilibrium.